Pengaruh Game Online terhadap Kesantunan Berbahasa Siswa Kelas V SD Muhammadiyah Kalinampu 1 - Rahmat, Rahmat; Amaruddin, Hidar (Wacana Akademika: Majalah Ilmiah Kependidikan, 2025)
This study aims to determine the influence of online games on the language politeness of fifth-grade students at SD Muhammadiyah Kalinampu 1, located in Bobok Tempel, Seloharjo, Pundong, Bantul, Special Region of Yogyakarta. The background of this research refers to APJII (2023) data, which reported that out of 8,510 respondents, 23.29% had played online games, and 42.23% of them spent more than four hours per day engaging in gaming activities. This research employed a quantitative survey method with 33 fifth-grade students from SD Muhammadiyah Kalinampu 1 as respondents, selected using a total sampling technique. The research instrument was a Likert-scale questionnaire containing indicators for the online game variable and the language politeness variable. Data were collected through the direct distribution of questionnaires in the classroom and completed individually by the students. Data analysis was conducted using simple linear regression. The findings indicate that online games have a significant influence on language politeness, with an r-square value of 0.379, meaning that online games contribute 37.9% to students’ language politeness.